The Effect Of Giving Manure Type Growth Regulators On The Vegetative Phase Of Chili Plants (Capsicum Frutescens) - Uni Savira; Hilda Pratiwi; Mizan Maulana (PT. Banjarese Pacific Indonesia, 2026)
Cayenne pepper (Capsicum frutescens L.) is a horticultural commodity with high economic value and continuously increasing market demand. The success of cayenne pepper production is largely determined by vegetative growth in the early stages, which is influenced by the availability of nutrients and plant growth regulators. The use of manure as a source of organic matter and natural Plant Growth Regulators (PGRs) is expected to enhance vegetative growth. This study aimed to determine the effect of manure application and natural PGRs on the vegetative growth of cayenne pepper and to identify the treatment that produces the best growth.The research was conducted from December to January 2026 at the land of the Kopbun Suka Tani Sejahtera Business Research Center, Kota Juang District, Bireuen Regency. The study used a factorial Randomized Block Design (RBD) with a 4 × 3 pattern and three replications. The first factor was the dosage of manure consisting of 0 kg (control), 1 kg, 1.5 kg, and 2 kg per plant. The second factor was the type of natural PGR, consisting of shallot extract, rice water, and coconut water. The observed parameters included plant height, number of leaves, leaf width, and number of branches at 15, 30, and 45 days after planting (DAP). Data were analyzed using the F-test and continued with the Honestly Significant Difference (HSD) test at a 5% significance level if the results were significant.The results showed that manure application had no significant effect on all vegetative growth parameters up to 45 DAP. The application of natural PGRs also showed no significant effect at 15, 30, and 45 DAP, as well as on other parameters. There was no significant interaction between manure and natural PGRs on all observed parameters.